Kelompok Sel Virtual sebagai Antisipasi disaat Pandemi Covid-19 - David Harahap; Jakob Maruliasi Simanungkalit; Selfina Bangla (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Abstract: This paper is backgrounded by the narrowness of ecclesiastical activities carried out face-to-face during the Covid-19 Pandemic. Limited face-to-face worship activities in the church, so this paper aims to offer an idea of a virtual cell group to become a place for worship to be carried out online. This virtual cell group is also an opportunity for the church in the development of digital ministries. In outlining this topic, researchers apply qualitative methods with a literature study approach as a primary source in obtaining data. The description of the discussion on this topic suggests that the purposes of the cell groups in the Bible include shepherding, making disciples, uniting, and saving souls. In the context of virtual cell groups, it is also done only technologies such as Google Meet, Facebook, Youtube and even Zoom as a means of forming virtual cell groups. The application of virtual cell groups does not hinder ecclesiastical activities, in carrying out its programs while maintaining the formation of congregational faith in the midst of the Covid-19 pandemic situation.Keyword: Cell Groups, Digital, Covid-19, PandemicAbstrak: Tulisan ini dilatar-belakangi oleh sempitnya aktivitas gerejawi dilakukan secara tatap muka dimasa Pandemi Covid-19. Terbatasnya kegiatan peribadatan secara tatap muka di gereja, maka tulisan ini bertujuan menawarkan sebuah gagasan kelompok sel virtual menjadi wadah peribadatan dilakukan secara daring. Kelompok sel virtual ini juga sekaligus sebagai kesempatan bagi gereja dalam pengembangan pelayanan digital. Di dalam menguraikan topik ini, peneliti menerapkan metode kualitatif dengan pendekatan studi literatur sebagai sumber primer dalam memperoleh data. Uraian pembahasan pada topik ini mengemukakan bahwa tujuan kelompok sel di dalam Alkitab di antaranya menggembalakan, memuridkan, menyatukan, dan menyelamatkan jiwa. Dalam konteks kelompok sel virtual, hal itu pun dilakukan hanya teknologi seperti Google Meet, Facebook, Youtube dan bahkan Zoom sebagai sarana membentuk kelompok sel virtual. Penerapakan kelompok sel virtual tidak menghalangi aktivitas gerejawi, dalam menjalankan program-programnya sekaligus menjaga pembinaan iman jemaat di tengah situasi pandemi Covid-19.Kata Kunci: Kelompok Sel, Digital, Covid 19, Pandemi